علاقة الضغوط المهنية بالاحتراق النفسي لدى الكادر التمريضي الشبه طبي: دراسة ميدانية بمستشفي مدينة شلغوم العيد ولاية ميلة - بن عمارة، سعيدة Bin Amarah, Saidah (جامعة محمد لمين دباغين سطيف 2, 2022)
هدفت هذه الدراسة إلى التعرف على العلاقة بين الضغوط المهنية والاحتراق النفسي لدى الكادر التمريضي الشبه طبي بمستشفى مدينة شلغوم العيد ولاية ميلة، وقد أجريت هذه الدراسة على عينة تتكون من 60 ممرضا وممرضة يعملون في مستشفى مدينة شلغوم العيد ولاية ميلة، كما اعتمدت الدراسة الاستمارة كأداة لقياس الضغوط المهنية، تم إخضاعها لإجراءات التقنين من حيث الثبات والصدق، وكذا مقياس ماسلاش لقياس مستوى الاحتراق النفسي، وقد أظهرت نتائج الدراسة وجود علاقة ارتباطية ضعيفة بين الضغوط المهنية والاحتراق النفسي لدى الكادر التمريضي الشبه طبي بمستشفى مدينة شلغوم العيد ولاية ميلة. This study aims to identify the relationship between professional pressures and burnout among paramedical nurses at Chelghoum Laid hospital, wilaya of Mila, and this study was carried out on a sample of 60 nurses. The study also approved the questionnaire as a tool for measuring professional pressures; it has been exposed to coding procedures in terms of reliability and validity, as well as the Maslach scale to measure the level of burnout. The results of the study showed that there is a strong correlation between professional pressures and burnout among paramedical nurses at the hospital in the city of Chelghoum Laid, wilaya of Mila.
Keywords: التنمية المهنية -- الكوادر الطبية -- المستشفيات الجزائرية -- الاضطرابات النفسية